Genotoxic and mutational potential of monocyclic terpenoids (carvacrol, carvone and thymol) in Drosophila melanogaster. - Nesterkina, M.; Bilokon, S.; Alieksieieva, T.; Kravchenko, I.; Hirsch, A.K.H. (Toxicology reports, 2023)
Genotoxicity and mutagenicity of monoterpene carvone along with the related monoterpene alcohols - carvacrol and thymol have been studied using Drosophila melanogaster as model system. The viability, pre-imaginal stage duration, level of dominant lethal mutations, unequal crossover in the Bar mutant of D. melanogaster and the influence of monocyclic terpenoids on the multiplication of the nuclear genome in salivary gland cells were investigated. The compounds tested after oral administration (0.02% in 1,2-propylene glycol) influence the degree of chromosome polyteny in salivary gland cells of D. melanogaster larvae. Among the terpenoids examined, carvacrol exhibited the most significant impact on imago lifespan, frequency of dominant lethal mutations, unequal crossover in the Bar mutant when added to the culture medium. Oral administration of terpenoids increases the average level of chromosome polyteny with the highest value for carvacrol - 1178 C compared to control (776 C). The conceivable mechanism of action for monocyclic terpenoids associated with the impact on juvenile hormone activity is debated.